The Influence of Accounting Students' Knowledge and Perceptions on the Implementation of Carbon Tax in Indonesia - Irvana Syintia Loka; Trias Arimurti; Novy Trianthy Noegraha (STIE Amkop Makassar, 2026)
The purpose of this study was to examine accounting students' understanding and perceptions of the implementation of the carbon tax in Indonesia. This study employed a descriptive quantitative approach, utilizing primary data obtained from one hundred accounting students at Buana Perjuangan University, Karawang. The Partial Least Squares Structural Equation Modeling (PLS-SEM) data analysis method was used. The study results showed that accounting students' knowledge significantly impacted carbon tax implementation, with a coefficient value of 0.776 and a p-value of 0.000 (<0.05). Conversely, student perceptions did not significantly impact carbon tax implementation, with a p-value of 0.052 (>0.05). Simultaneously, the knowledge and perception variables were able to explain 36.5% of the variability in carbon tax implementation. These findings indicate that cognitive elements, specifically understanding and environmental fiscal literacy, play a greater role in supporting carbon tax policy implementation than accounting students' subjective perceptions.